Development of a multigenerational energy system for clean hydrogen generation - Karapekmez, Aras; Dincer, Ibrahim (ELSEVIER SCI LTD, 2021)
The existing fueling options for many power plants are still dependent primarily on fossil fuel resources, which in return cause serious local and global environmental problems. Therefore, in order to reduce the detrimental effects of greenhouse gas emissions, the use of cleaner production methods has been accelerated to develop and implement environmentally-friendly energy systems. In this regard, the combination of renewable energy systems and hydrogen production methods will definitely play a crucial role in the energy sector's transition to a carbon-free production. In order to make the use of geothermal energy cleaner and more sustainable, some obstacles need to be eliminated. Most impor-tantly, the hydrogen sulfide emissions may cause serious concerns in public acceptance of geothermal power plants. In the current study, solar, wind and geothermal energy resources are integrated to develop an integrated renewable-based energy system with a key objective of higher environmental and system performance. The underlying motivation is to propose a model which consists of a hydrogen sulfide abatement unit and an electrolyzer to produce hydrogen from hydrogen sulfide and hence eli-minites the hydrogen sulfide emissions. A detailed thermodynamic analysis is carried out using Engi-neering Equation solver (EES) software. In addition, the effects of key design parameters and operating conditions (such as wind inlet speed and average hourly solar radiation) are analyzed, and their effects on the system overall performance are investigated. When 60 kg/s of geothermal fluid is supplied to the designed system, assuming that the NCG composition is equal to 15%, 0.7388 kg hydrogen sulfide will be emitted and 0.0433 kg hydrogen will be produced per second. The first-law (energy) and second-law (exergy) efficiencies are found to be 52.97% and 55.69% respectively. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Renewable energy; Cleaner production; Multigeneration; Hydrogen; Electrolysis; Solar; Wind; Exergy; GEOTHERMAL HEAT-SOURCE; SULFIDE; PERFORMANCE; DRIVEN; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology